Malnutrition-Inflammation Score (MIS) and Physical Activity among Hemodialysis Patients in Dr. Hasan Sadikin General Hospital Bandung - Rizka Putri Hamuktiono; Rudi Supriyadi; Nida Suraya (Althea Medical Journal, 2015)
Background: Protein Energy Malnutrition (PEM) related to inflammation and physical activities reduction occur commonly among hemodialysis patients. This study aimed to describe Malnutrition-Inflammation Score (MIS) and physical activity of hemodialysis patients.Methods: This study involved 117 patients in the Hemodialysis Unit of Dr. Hasan Sadikin General Hospital Bandung from September to October 2014. Secondary data were collected to examine MIS and physical activity, which was measured by using Baecke Physical Activity Questionnaire. The collected data were presented using frequency distribution.Results: Eighty (68.4%) patients had MIS <6, thirty seven (31.6%) patients had MIS ≥6, and ninety four (80.3%) patients had light physical activity.Conclusions: Most of the patients have MIS <6 and are physically inactive. [AMJ.2015;2(4):601–7] DOI: 10.15850/amj.v2n4.478